The Impact of Industrialization in Improving the Quality of Basic Human Resources Digitalization on the Indonesian Economy - Dela Fitri Nurmaya; Beny Mahyudi Saputra (Eduvest - Journal of Universal Studies, 2025)
Globalization and reform have had a major influence on environmental policy. Globalization and reform have changed values and mindsets regarding environmental policy making. This research aims to investigate the impact of industry on the social interactions of local communities and the factors that influence these social interaction patterns. The research method for the application created uses descriptive data, collection techniques. In general, the descriptive approach is a data collection technique, of how many research subjects are involved in using the system according to system requirements regularly and adjusted to existing facts so that it is accurate. Descriptive research aims to describe a situation or phenomenon as it is. The phenomenon of environmental issues related to negative impacts caused by industrial activities also influences company management to make policies regarding improving performance. Changes to, environmental permits in business activities as regulated in Law Number 11 of 2020 concerning Job Creation are considered to have more of a goal of improving economic welfare than providing environmental protection and management in Indonesia which was previously regulated in Law Number 32 of 2009 concerning Protection and Environmental Management. This assessment emerged as a result of changing the concept of Environmental Permit to Environmental Approval and weakening community participation. This is a concern for the Indonesian people, especially regarding the regulation of environmental permits, business activities and their impact on environmental protection and management in Indonesia after the enactment of the Job Creation Law.